2015
DOI: 10.1080/02726351.2014.978425
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on the Stability of Alumina and Silica Nanosuspension Produced by Wet Grinding

Abstract: Effects of suspension pH on stability and surface properties of alumina and silica nanosuspension were investigated. Nanosuspensions of alumina and silica used in the present study were produced by wet grinding in stirred media mill. The electrostatic stabilization of two types of nanosuspension was conducted by zeta potential and turbiscan analysis as a function of pH. The long term stability analysis of alumina and silica nanosuspension was investigated using an optical analyzer. It was observed that particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Micromilling is a new nanotechnology that has enabled production of particles with median diameters (D50s) from the submicrometer range down to hundreds of nanometers, and even smaller (Mende et al 2003(Mende et al , 2004. This technology has been applied to materials such as corundum (Stenger et al 2005), aluminum nitride (Jia et al 2015, Qiu et al 2006, Li4Ti5O12 (Han et al 2012), barium sulfate (Patel et al 2014), silica (Patel et al 2015), and crystalline pyrene (Flach et al 2016). Our research group (Pan et al 2015) and others (Amaral et al 2016 have produced AC particles with D50s of 200-250 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Micromilling is a new nanotechnology that has enabled production of particles with median diameters (D50s) from the submicrometer range down to hundreds of nanometers, and even smaller (Mende et al 2003(Mende et al , 2004. This technology has been applied to materials such as corundum (Stenger et al 2005), aluminum nitride (Jia et al 2015, Qiu et al 2006, Li4Ti5O12 (Han et al 2012), barium sulfate (Patel et al 2014), silica (Patel et al 2015), and crystalline pyrene (Flach et al 2016). Our research group (Pan et al 2015) and others (Amaral et al 2016 have produced AC particles with D50s of 200-250 nm.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that NS particles are highly aggregated and irregular shaped at pH value below 9. 34 …”
Section: Resultsmentioning
confidence: 99%
“…Unlike silica, alumina nanoparticle exhibits positively charged particles when dispersed in an aqueous medium at neutral pH value. Patel et al, 2015, measured the zeta potential of the suspensions of alumina and silica nanoparticle. The results observed a positively charged alumina suspension of +20 mV as opposed to -30 mV obtained from silica with the same particle concentration.…”
Section: Freshwater-based Mudsmentioning
confidence: 99%
“…The results observed a positively charged alumina suspension of +20 mV as opposed to -30 mV obtained from silica with the same particle concentration. However, the zeta potentials decreased with the increasing pH levels due to the deprotonation of the particle surfaces, and at pH 11, zeta potentials of -15 mV and -50 mV were observed from alumina and silica, respectively (Adair et al, 2001;Patel et al, 2015). Zeta potential is a measure to determine the surface charge of particles in colloidal suspension.…”
Section: Freshwater-based Mudsmentioning
confidence: 99%